Seismic Analysis of Non-Regular Structures Based on Fragility Curves: A Study on Reinforced Concrete Frames - Giovanni Smiroldo; Marco Fasan; Chiara Bedon (Buildings)
The seismic performance and expected structural damage in reinforced concrete (RC) frames, as in many others, is a critical aspect for design. In this study, a set of RC frames characterized by increasing in-plan and in-height non-regularity is specifically investigated. Four code-conforming three-dimensional (3D) buildings with varying regularity levels are numerically analyzed. Their seismic assessment is conducted by using unscaled real ground motion records (61 in total) and employing non-linear dynamic simulations within the Cloud Analysis framework. Three distinct intensity measures (IMs) are used to evaluate the impact of structural non-regularity on their seismic performance. Furthermore, fragility curves are preliminary derived based on conventional linear regression models and lognormal distribution. In contrast with the initial expectations and the typical results of non-linear dynamic analyses, the presented comparative results of the fragility curves show that the non-regularity level increase for the examined RC frames does not lead to progressively increasing fragility. Upon these considerations on the initial numerical findings, a re-evaluation of the methodology is performed using a reduced subset of ground motion records, in order to account for potential biases in their selection. Moreover, to uncover deeper insights into the unexpected outcomes, a logistic regression based on a maximum likelihood estimate is also employed to develop fragility curves. Comparative results are thus critically discussed, showing that the herein considered fragility development methods may lead to seismic assessment outcomes for code-conforming non-regular buildings that are in contrast with those of raw structural analyses. In fact, the considered building code design provisions seem to compensate non-regularity-induced torsional effects.